Salivary Cortisol and DHEA Levels in the Korean Population: Age-Related Differences, Diurnal Rhythm, and Correlations with Serum Levels - Ahn, Ryun-Sup (Yonsei University College Medicine, 2007)

(untitled)
PURPOSE: The primary objective of this study was to examine the changes of basal cortisol and DHEA levels present in saliva and serum with age, and to determine the correlation coefficients of steroid concentrations between saliva and serum. The secondary objective was to obtain a standard diurnal rhythm of salivary cortisol and DHEA in the Korean population. MATERIALS AND METHODS: For the first objective, saliva and blood samples were collected between 10 and 11 AM from 359 volunteers ranging from 21 to 69 years old (167 men and 192 women). For the second objective, four saliva samples (post-awakening, 11AM, 4PM, and bedtime) were collected throughout a day from 78 volunteers (42 women and 36 men) ranging from 20 to 40 years old. Cortisol and DHEA levels were measured using a radioimmunoassay (RIA). RESULTS: The morning cortisol and DHEA levels, and the age-related steroid decline patterns were similar in both genders. Serum cortisol levels significantly decreased around forty years of age (p < 0.001, when compared with people in their 20s), and linear regression analysis with age showed a significant declining pattern (slope = -2.29, t = -4.297, p < 0.001). However, salivary cortisol levels did not change significantly with age, but showed a tendency towards decline (slope = -0.0078, t = -0.389, p = 0.697). The relative cortisol ratio of serum to saliva was 3.4-4.5% and the ratio increased with age (slope = 0.051, t = 3.61, p < 0.001). DHEA levels also declined with age in saliva (slope = -0.007, t = -3.76, p < 0.001) and serum (slope = -0.197 t = -4.88, p < 0.001). In particular, DHEA levels in saliva and serum did not start to significantly decrease until ages in the 40s, but then decreased significantly further at ages in the 50s (p < 0.001, when compared with the 40s age group) and 60s (p < 0.001, when compared with the 50 age group). The relative DHEA ratio of serum to saliva was similar throughout the ages examined (slop = 0.0016, t = 0.344, p = 0.73). On the other hand, cortisol and DHEA levels in saliva reflected well those in serum (r = 0.59 and 0.86, respectively, p < 0.001). The highest salivary cortisol levels appeared just after awakening (about two fold higher than the 11 AM level), decreased throughout the day, and reached the lowest levels at bedtime (p < 0.001, when compared with PM cortisol levels). The highest salivary DHEA levels also appeared after awakening (about 1.5 fold higher than the 11AM level) and decreased by 11AM (p < 0.001). DHEA levels did not decrease further until bedtime (p = 0.11, when compared with PM DHEA levels). CONCLUSION: This study showed that cortisol and DHEA levels change with age and that the negative slope of DHEA was steeper than that of cortisol in saliva and serum. As the cortisol and DHEA levels in saliva reflected those in serum, the measurement of steroid levels in saliva provide a useful and practical tool to evaluate adrenal functions, which are essential for clinical diagnosis.